Implementation of Principal Supervision in Developing the Competence of Education Personnel at SMA Negeri 1 Pangale, Central Mamuju Regency - Ummi Rahmah; St Syamsudduha; Musdalifah Musdalifah (Journal of Pedagogi, 2024)
This study aims to analyze: 1) the planning of principal supervision at SMA Negeri 1 Pangale, Central Mamuju Regency, 2) the implementation of principal supervision, and 3) the reporting and follow-up of supervision at the same institution. Employing qualitative research, the study explores the specific conditions and situations at SMA Negeri 1 Pangale. Data sources include the Principal, Deputy Principal, and education staff, collected through observation, interviews, and documentation. Data processing and analysis follow three stages: data reduction, data presentation, and conclusion drawing. The findings reveal: 1) Supervision planning involves setting goals, scheduling, determining targets, and choosing appropriate supervision techniques. 2) Implementation comprises steps for supervision, identifying key aspects, executing supervision activities, and evaluating results. 3) Reporting and follow-up entail compiling and summarizing supervision results into reports, suggesting improvements, and conducting monitoring. Implications of the study suggest: 1) Principals should enhance their competencies by identifying training and development opportunities for staff. 2) Education staff should continuously improve their performance to provide better services. This comprehensive approach to supervision ensures that SMA Negeri 1 Pangale achieves its educational objectives while fostering professional growth among its personnel.